PENINGKATAN HASIL BELAJAR TOLAK PELURU DENGAN PENDEKATAN BERMAIN PADA SISWA KELAS VI SD NEGERI 01 SAMPANG KECAMATAN KARANGTENGAH KABUPATEN DEMAK TAHUN PELAJARAN 2012 / 2013 - Arif Nugroho, Wiwin (Jurnal Phederal Penjas, 2013)
Wiwin arif nugroho, ENHANCEMENT OF LEARNING APPROACH TO PLAY WITH BULLETS REJECT CLASS VI STUDENT AFFAIRS 01 SAMPANG SD SUB KARANG TENGAH DEMAK REGENCY. Thesis, Surakarta Faculty of Teacher Training of Education, University of March Surakarta, October 2012/2013.This study aims to determine the increase in learning out comes shot putthrough sixth grade elementary scool students play district 01 Sampang scool year 2012/2013.This study uses Classroom Action Research (CAR)the data source of this research is the sixth grade elementary scool students 01 Sampang scool years 2012/2013.Amounted to 16 people consisting of 8 students and 8 girl by boys.Data collection techniques with observation and assessment of learning outcomes shot put.Data analysis techniques used in this research is descriptive quantitative analysis based on percentage.Based on the results obtained that learning to play approach, can improve learning outcomes shot put sixth grade elementary shcool students 01 Sampang scool year 2012/2013.From the analysis results a significant improvement from the first cycle and second cycle. Learning outcome before getting action shot put 43,75% with is complete category,while students who complete 15 students.Conclusions from this research that there is an increase from baseline to the first cycle and second cycle, both from an increase in value and the value of learning outcomes, mastery of learning outcomes . The everage value of learning out come in the initial conditions (70.16),the firs cycle (76.28) and second cycle (81.44), so the increase of the initial conditions for the second cycle of (11.28). While the value of mastery learning so the increase of the initial conditions (43.75%), cycle 1 (62.50%) and second cycle (97.75%), so the increase of the initial conditions for the second cycle of (50%). Thus, it can be concluded with the playing approach can improve students learning outcomes shot put sixth grade elementary scool lesson 01 Sampang year 2012/2013.Keywords: Reject bullet, approach play, learning Outcome.